Actividad Social. (UNED, 2023)
De izquierda a derecha, se encuentran a Álvaro Palma Campos, Roxana Cruz Zúñiga (Secretaria de operaciones), Evelyn Brenes Rojas, Grace Alfaro Alpízar, Jeannette Jiménez Vargas, Xinia Zuñiga Muñóz